Impact des changements climatiques et de la fréquentation humaine sur la biodiversité des îles subantarctiques françaises - Yves Frenot; Marc Lebouvier; Jean-Claude Gloaguen; Françoise Hennion; Philippe Vernon; Jean-Louis Chapuis (Belgeo)
Biological invasions, in connection with climate changes, are amongst the most significant threats to biodiversity worldwide. Even in antarctic and subantarctic regions, alien species arrived since the end of the 18th century. Most of these introductions are obviously associated with human activities and ship landings. Otherwise, as predicted by many global circulation models, rates of warming are expected to be stronger at higher latitudes. Our study on the Kerguelen Islands confirms this trend and demonstrates that the effects of warming (+ 1.3°C since the mid 1960s) and summer droughts on plants and invertebrates are now visible. With climate change occurring rapidly, both the numbers of introductions and the success of colonisation by alien species are likely to increase, with as consequence subsequent impacts on the entire ecosystem.